Mobile Picture Dictionary Application With Text Pronunciation - Kamil, Muhd Asnawi; Mahamad, Saipunidzam (Journal of Computing Technologies and Creative Content, 2016)
In Malaysia, lower primary school students have been using the picture dictionary as the guide to learn objects in multiple languages such as Malay, English, Chinese and Tamil. Not only that, teachers also have been using it as a material to assist them in teaching language subjects. Some of the learning activities that involved the usage of picture is dictionary in school is sentence construction, vocabulary learning, arts drawing, and crucial activity such as oral assessment. Not only that, students also have been using picture as a source of exploring and discovering new things. However, the picture dictionary is lacking few things which can be improved with an introduction of an application which is called picture dictionary mobile application with text pronunciation. Traditional picture dictionary can be really heavy for children to carry. Not only that, it does not allow children to search what their want easily in the dictionary. Lastly, even though it taught student what certain objects are, it does not teach them on how to pronounce the word correctly. In this project, the first objective is to study what is picture dictionary and to analyze the importance of picture dictionary. Fifty questionnaire forms were done and distributed to two schools which are Sekolah Kebangsaan Tronoh and Sekolah Kebangsaan Seri Tronoh. Questions were also asked to collect information about the picture dictionary mobile application that is going to be developed. At the end of the research, it was found that the responses are convincing that picture dictionary mobile application is a good application to be developed in assisting in lower primary school students learning. This leads to Primary objective,which can assist lower primary school children in learning languages such as malay,English,Chinese and Tamil.